2008
DOI: 10.1007/s10461-007-9350-4
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship-Oriented Information-Motivation-Behavioral Skills Model: A Multilevel Structural Equation Model among Dyads

Abstract: Transmission rates of HIV infection have increased steadily among heterosexual adults, however current theoretical models have not been tested statistically at the dyadic level in which risk behaviors occur. The purpose of the current study was to test an Information-Motivation-Behavioral skills (IMB) model of HIV risk behavior (IMB) specifically articulated for heterosexual couples in established relationships using data from both members of 75 dyads. The multilevel relationship-oriented information-motivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…Interventions that directly train couples to discuss issues related to HIV-transmission and prevention (the third approach) are less common, but several recent efforts have been moving in this direction [14, 18, 2628]. For example, Project CONNECT [14], one of the first studies to examine couples-focused STI/HIV prevention, found that an intervention that directly trained women, and in one group their partners as well, to communicate about condom use (the first and third approach) led to more consistent condom use, compared to a control condition that did not include such training.…”
Section: Dyads In Existing Hiv-prevention Effortsmentioning
confidence: 99%
“…Interventions that directly train couples to discuss issues related to HIV-transmission and prevention (the third approach) are less common, but several recent efforts have been moving in this direction [14, 18, 2628]. For example, Project CONNECT [14], one of the first studies to examine couples-focused STI/HIV prevention, found that an intervention that directly trained women, and in one group their partners as well, to communicate about condom use (the first and third approach) led to more consistent condom use, compared to a control condition that did not include such training.…”
Section: Dyads In Existing Hiv-prevention Effortsmentioning
confidence: 99%
“…Motivation to engage in safer sex behavior is related to shared social norms, beliefs, and attitudes within the couple rather than solely at the individual level. 31 The goal of this study was to gain in-depth information on contextual and relationship-level influences on sexual decision making and use of risk-reduction strategies among heterosexual STI clinic patients. We conducted focus groups to gain perspectives on use and motivations for sexual agreements and other risk-reduction strategies and the role of relationship dynamics in negotiation of sexual risk among heterosexual young adults.…”
Section: Introductionmentioning
confidence: 99%
“…This has proven to be more arduous when practicing preventive sex with a steady partner than with a casual one (Harmann and Amico 2009). However, given the inherent dyadic nature of most HIV transmissions, it is essential to consider sexual behaviors in terms of the individual the partner, and the dyad as well (Eaton et al 2009).…”
Section: Challenges For Hiv Couplesmentioning
confidence: 99%
“…The literature suggests that being in an intimate relationship is associated with many barriers to practicing safer sex (El-Bassel et al 2001), that the use of condoms in stable relationships is not a usual practice (Harmann and Amico 2009), and that transmission within regular, established discordant relationships is higher than within non-regular discordant relationships (Kalichman et al 2002). Regardless of the HIV status of the couple, sexual transmission risk reduction strategies must be openly discussed with both spouses.…”
Section: Living Intimacy and Sexuality With Serodiscordancementioning
confidence: 99%